Organizing for societal grand challenges - Gümüsay, Ali Aslan; Marti, Emilio; Trittin-Ulbrich, Hannah; Wickert, Christopher (Research in the sociology of organizations ;, 2022)
The ebook edition of this title is Open Access and freely available to read online. Societal grand challenges have moved from a marginal concern to a mainstream issue within the field of organization and management studies. Organizing for Societal Grand Challenges unpacks how diverse forms of organizing help tackle - or reinforce - grand challenges, while emphasizing the need for researchers to expand their methodological repertoire and reflect upon scholarly practices. This edited collection offers an organizational perspective on societal grand challenges in three sections: Diverse Forms of Organizing and Societal Grand Challenges; Scholarship and Societal Grand Challenges; Reflections and Outlook. The articles offer empirical and conceptual work that focus on a wide variety of regions including Africa, Asia, Europe, and South America, and engage with multiple grand challenges, such as the COVID-19 pandemic, decent work, hunger, inequality, and poverty. Drawing on varied theoretical lenses, the authors take stock of recent developments in the literature, present an overview of the current thinking, and set a foundation for future research on grand challenges in organization and management studies. The articles provide inspiration, insights, and instruments for developing timely and relevant knowledge to engage with the pressing societal grand challenges of our time.